Immature dendritic cells navigate microscopic mazes to find tumor cells. Issue 9 (1st April 2019) - Um, Eujin; Oh, Jung Min; Park, Juhee; Song, Taegeun; Kim, Tae-Eon; Choi, Yongjun; Shin, Changsik; Kolygina, Diana; Jeon, Jae-Hyung; Grzybowski, Bartosz A.; Cho, Yoon-Kyoung
Abstract : Imposing physical confinements in the migration tracks of dendritic cells reveals different migratory behaviors towards cancer vs. normal cells. Abstract : Dendritic cells (DCs) are potent antigen-presenting cells with high sentinel ability to scan their neighborhood and to initiate an adaptive immune response. Whereas chemotactic migration of mature DCs (mDCs) towards lymph nodes is relatively well documented, the migratory behavior of immature DCs (imDCs) in tumor microenvironments is still poorly understood. Here, microfluidic systems of various geometries, including mazes, are used to investigate how the physical and chemical microenvironment influences the migration pattern of imDCs. Under proper degree of confinement, the imDCs are preferentially recruited towards cancer vs. normal cells, accompanied by increased cell speed and persistence. Furthermore, a systematic screen of cytokines, reveals that Gas6 is a major chemokine responsible for the chemotactic preference. These results and the accompanying theoretical model suggest that imDC migration in complex tissue environments is tuned by a proper balance between the strength of the chemical gradients and the degree of spatial confinement.